Psychometric Properties of the Classroom English Proficiency (CEP) Scale for English Language Teachers in Indonesia: A CFA and Rasch Model Analysis - Syahadah Albaqiyatul Karimah; Devie Yundianto; Muhammad Aqil Alaauddin (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
This study aimed to adapt and validate the Classroom English Proficiency Scale (CEPS) for English language teachers in Indonesia using Confirmatory Factor Analysis (CFA) and the Rasch Rating Scale Model (RSM). The CFA confirmed that the four latent dimensions—Grammar, Pronunciation, Interaction, and Instruction—fit well within a second-order structure representing a single construct of classroom English proficiency. Rasch analysis further supported the unidimensionality assumption, with variance explained by measures exceeding the recommended criterion. The scale showed high reliability, and all items met model-fit expectations. The five-point Likert rating scale functioned effectively, with ordered Andrich thresholds and consistent category use. Differential Item Functioning (DIF) analysis indicated that 11 of 12 items were invariant across gender groups, except CEPS_2 (“I can use a wide range of English vocabulary”), which was slightly more difficult for male respondents. Overall, the Indonesian-adapted CEPS demonstrated strong validity, reliability, and fairness, confirming its suitability for assessing English proficiency in classroom contexts. The CEPS can serve as a reliable diagnostic and evaluative tool for English language teachers in teacher education and EFL assessment settings.